The impacts of chrononutrition and food on the menstrual cycle (Research, Society and Development, 2024)
The circadian cycle is the body's mechanism for adjusting to the duration of day and night. Through biological clocks, the human body can adapt physiological processes to daily cyclic events. Imbalances in these clocks can have negative impacts on the body, resulting in metabolic disorders. The development of symptoms stemming from premenstrual syndrome depends, among other factors, on the relationship with dietary intake patterns, which can exacerbate or alleviate these symptoms. The application of chrononutrition as a therapeutic intervention in restoring homeostasis and alleviating menstrual period symptoms has shown promise. Thus, the aim of this research is to analyze the impacts of dietary patterns on menstrual cycle phases, as well as to investigate the potential of chrononutrition within this cycle. The databases consulted include SCIELO, EBSCO, CAPES, and PUBMED. Research in general indicates a direct influence of biological clocks on metabolic functions, while also emphasizing that dietary patterns serve as a foundation for hormonal metabolism, demonstrating the effectiveness of therapeutic application of chrononutrition in menstrual cycle phases and the possibility of symptom alleviation. However, there is still a scarcity of studies on the subject, which complicates the establishment of a more assertive nutritional strategy. Therefore, it was observed that research in general demands greater investment in the topic for chrononutrition to indeed be established as a treatment for alleviating symptoms during the menstrual period.